An Integrate Approach in Management of Diabetes Mellitus (International Journal of Ayurveda and Pharma Research, 2024)
Madhumeha comes under category of Yapya disease. There are very few medicines described in texts for Madhumeha, Svarnamaksika and Shilajita are among of them Rasayana treatment is usually beneficial in yapya diseases. Svarnamaksika is considered as one of the best Rasayana among all Rasayana.[1]  Svarnamaksika improves microcirculation of Rasa dhatu because of having properties like Vyavayi and Laghu. In this case, patient was given Svarnamaksikayoga which contains Svarnamaksika and Salasaradi group which is described in Susruta Samhita. A patient 22-year-old was diagnosed as type 2 diabetes mellitus and after taking 1-year treatment of type 2 DM, she didn’t get any relief and her blood sugar was increasing. Then, she was prescribed insulin when she came for Ayurveda treatment. During first follow-up of 7 days, her blood sugar level was normal so insulin was stopped and she was kept on oral hypoglycemic agent and Ayurveda treatment. After 4 months, her blood sugar level reached to normal level and she was advised to continue Ayurveda treatment only. The collected data of this study suggest that earlier intervention of Ayurveda treatment can reverse the disease process in treatment of insulin dependent diabetes mellitus.